UPAYA MENGURANGI KETERGANTUNGAN GADGET MELALUI KETRAMPILAN MENARI (SISWA SD KEPEL KOTA PASURUAN) - Erwantiningsih, Eni; Nabil, Disa; Maudy, Maudy (Yayasan Education and Social Center, 2023)
Online learning, which is an option during the pandemic, not only has a positive influence on Kepel Elementary School students in Pasuruan City in getting to know technology, but also has an influence that needs to be of concern to all parties, namely children's dependence on gadgets, so that children interact less intensely with both parents and friends. . This service aims to provide positive activities as a way to reduce student dependence on gadgets and provide assistance so that students do not feel bored and fed up during online learning. The methods used are problem surveys, scheduling and recruiting participants, training processes, uploading videos to social media and delivering social media links to schools. The object is Kepel State Elementary School students from grades 3 to 5, totaling 8 children. Dance practice time is held every Sunday morning so as not to interfere with learning time at school. The results of the service showed that after participating in this dancing activity, students became happy and did not get bored during online learning, their bodies became healthier and the intensity of gadget use was in accordance with school requirements because they were busy memorizing dance material